2013
DOI: 10.1007/s12471-013-0430-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with atorvastatin is associated with a better prognosis in chronic heart failure with systolic dysfunction: results from The Daunia Heart Failure Registry

Abstract: BackgroundFew works have evaluated the effect of statins on left ventricular dysfunction in patients with chronic heart failure (CHF), by using tissue Doppler imaging (TDI). We therefore aimed to investigate whether atorvastatin treatment may influence prognosis and myocardial performance evaluated by TDI in subjects with CHF.MethodsFive hundred thirty-two consecutive CHF outpatients enrolled in a local registry, the Daunia Heart Failure Registry, were prospectively analysed. 195 patients with CHF and left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…Statins — 3-hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase inhibitors — are a class of cholesterol-lowering drugs that also reduce the incidence of postoperative AF, left ventricular dysfunction, and maladaptive tissue remodeling with their pleiotropic effects independent of cholesterol-lowering [2124]. Statins recently were demonstrated to dephosphorylate signaling proteins by activating PP2A or PPM1A in extra-cardiac liver cell lines and neurons [2528].…”
Section: Introductionmentioning
confidence: 99%
“…Statins — 3-hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase inhibitors — are a class of cholesterol-lowering drugs that also reduce the incidence of postoperative AF, left ventricular dysfunction, and maladaptive tissue remodeling with their pleiotropic effects independent of cholesterol-lowering [2124]. Statins recently were demonstrated to dephosphorylate signaling proteins by activating PP2A or PPM1A in extra-cardiac liver cell lines and neurons [2528].…”
Section: Introductionmentioning
confidence: 99%
“…20) Treatment with atorvastatin, in particular, has been shown to be superior in preventing and treating cardiovascular disease. [21][22][23] Correlation analysis suggested that Tregs frequency and function positively are correlated with left ventricular ejection fraction, but negatively correlated with left ventricular end-diastolic dimension and Nterminal pro-brain natriuretic peptide (NT-proBNP) in patients with CHF. 24) Zhang, et al 25) demonstrated that atorvastatin treatment was associated with reduced all-cause mortality and readmission rate for heart failure (HF), and the superiority of statin therapy was significant in CHF patients younger than 65 years.…”
mentioning
confidence: 99%
“…Atorvastatin and pravastatin are members of the drug class known as stains used to lower cholesterol. It has been suggested that the use of atorvastatin or pravastatin in HF patients attenuates adverse left ventricular remodeling and improves left ventricular systolic function as well as clinical outcomes (Sola et al, 2006; Wojnicz et al, 2006; Han et al, 2007; Lipinski et al, 2009; Correale et al, 2013). Bromocriptine is a prolactin release inhibitor.…”
Section: Resultsmentioning
confidence: 99%